Business in Action / Accompanied by SSweetco: A Resource and Activity File - Bittel R. Lester; Burke Ronald S; Hoke Pavey L (Mcgraw Hill Book Company, 1980)
The Nature of American Business, The Business System in America, The American Economy System, The American Business Environment, The Form and Structure of American Business, The Legal Forms of Business Ownership, Managerial Functions in a Business, Internal Structure of Business Organizations, Basic Business Operations - Marketing, Markets and Marketing, Marketing Distribution Systems, Marketing Promotion, Basic Business Operations - Production, Location and Layout and Management of Facilities, Production Materials Management, Basic Business Operations - Finance, Financial Management and Funding, Money Supply and Financial Institutions, Risk and Insurance and Credit Management, Basic Business Operations - Personnel, Personnel Administration, Human Resource Management, Labor Management Relations, Basic Business Operations - Information and Controls, Information Systems and Decision Making and Planning, Advanced Business Operations, Appendix, Glossary. Index.
The Nature of American Business, The Business System in America, The American Economy System, The American Business Environment, The Form and Structure of American Business, The Legal Forms of Business Ownership, Managerial Functions in a Business, Internal Structure of Business Organizations, Basic Business Operations - Marketing, Markets and Marketing, Marketing Distribution Systems, Marketing Promotion, Basic Business Operations - Production, Location and Layout and Management of Facilities, Production Materials Management, Basic Business Operations - Finance, Financial Management and Funding, Money Supply and Financial Institutions, Risk and Insurance and Credit Management, Basic Business Operations - Personnel, Personnel Administration, Human Resource Management, Labor Management Relations, Basic Business Operations - Information and Controls, Information Systems and Decision Making and Planning, Advanced Business Operations, Appendix, Glossary. Index.